Diversity of Dust Properties in External Galaxies Confirmed by Polarization Signals from Type II Supernovae - Nagao Takashi; Patat Ferdinando; Maeda Keiichi; Baade Dietrich; Mattila Seppo; Taubenberger Stefan; Kotak Rubina; Cikota Aleksandar; Kuncarayakti Hanindyo; Bulla Mattia; Maund Justyn (IOP Publishing, 2022)
Investigating interstellar (IS) dust properties in external galaxies is important not only to infer the intrinsic properties of astronomical objects but also to understand the star/planet formation in the galaxies. From the non–Milky Way–like extinction and interstellar polarization (ISP) observed in reddened Type Ia supernovae (SNe), it has been suggested that their host galaxies contain dust grains whose properties are substantially different from the Milky Way (MW) dust. It is important to investigate the universality of such non-MW-like dust in the universe. Here we report spectropolarimetry of two highly extinguished Type II SNe (SN 2022aau and SN 2022ame). SN 2022aau shows a polarization maximum at a shorter wavelength than MW stars, which is also observed in some Type Ia SNe. This is clear evidence for the existence of non-MW-like dust in its host galaxy (i.e., NGC 1672). This fact implies that such non-MW-like dust might be more common in some environments than expected, and thus it might affect the picture of the star/planet formation. On the other hand, SN 2022ame shows MW-like ISP, implying the presence of MW-like dust in its host galaxy (i.e., NGC 1255). Our findings confirm that dust properties of galaxies are diverse, either locally or globally. The present work demonstrates that further investigation of IS dust properties in external galaxies using polarimetry of highly reddened SNe is promising, providing a great opportunity to study the universality of such non-MW-like dust grains in the universe.